PELAKSANAAN PENDIDIKAN DAN PELATIHAN PROGRAM GENERASI BERENCANA (GENRE) PADA KANTOR PERWAKILAN BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL (BKKBN) DI PROVINSI RIAU - Aritonang, Veronika; Tua R.F.S, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The lack of socialization towards teens/students that impact the lack of knowledge about the problems that teens are very complex surrounding the Triad KRR (sexuality, HIV, AIDS, and Drugs). In addition also still lack of motivation and support from the education and Training Generasi Berencana Program (GenRe) that caused some factors.The aint of this research is to know the implementation of the education and Training of the GenRe Programs at Perwakilan Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) in Riau ProvinceThe concept of the theory that researchers use is the implementation of education and training where educational standards and implementation consists of training needs, goal setting, the determination of the content of the programmes, principles of learning, implementation of programs, the identification of benefits, and an assessment of the implementation of the program. This training using qualitative method with descriptive data review. In the data collection of researchers using the technique of interviewing, observation, and study of librarianship as a source of information.The results showed that the implementation of the education and Training GenRe have been concluded but not yet optimal. This is evidenced by the existence of training needs, goal setting, the determination of the content of the programmes, principles of learning, implementation of programs, the identification of benefits, and an assessment of the implementation of the program could not be implemented as a whole. As for restricting factors that affect the implementation of the education and training programs of the Genre is the participants of the education and training and also the cost that would be sure not required at the time of the implementation of education and training.Keywords: Education and Training, GenRe